Penyelesaian Perkara Isbat Nikah di Pengadilan Agama Kabupaten Kuningan Kelas 1A: (Studi Putusan Pengadilan Agama Kuningan No. 477/Pdt.P/2020/PA.Kng) - Madinah, Dina; Asari, Agus (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2025)
Marriage is proven by a marriage certificate, and each husband and wife has a copy. However, in practice, it is undeniable that until now there are still many illegal marriages which are often also called siri marriages (underhand marriages) because they are not officially recorded by the marriage registrar. This causes the marriage to not be registered at the Office of Religious Affairs (KUA) so this has an impact on the recording of the child's birth certificate. Based on this background, a problem is formulated, namely, how to settle the Marriage Isbat Case in the Islamic Religious Court of Kuningan District Class 1A and how the Legal Basis and Judges Consideration in the Settlement of Marriage Isbat Cases at the Kuningan Islamic Religious Court. The purpose of this study is to find out the factors that become the reasons for the Application for Marriage Isbat at the Kuningan Islamic Religious Court and to find out the Judges' Considerations in the Settlement of Marriage Isbat Cases at the Kuningan Islamic Religious Court. According to the Compilation of Islamic Law, marriage problems that are not registered at the KUA can be resolved through the Marriage Isbat submitted to the Religious Courts in accordance with the domicile. The method used in this study is a qualitative research method. The data collection techniques include observation, interview, and documentation techniques. The results showed that based on the decision of the Kuningan Religious Court No. 477/Pdt.P/2020/PA.Kng, it was known that Petitioner I and Petitioner II had married with the fulfillment of the conditions and pillars of marriage so that the marriage was legal according to Islamic law. However, because the marriage was not registered by the local KUA, the marriage was not registered. The consideration of the Panel of Judges in determining Marriage Isbat Number 477/Pdt.P/2020/PA.Kng is based on Article 2 of Law Number 1 of 1974, Article 6 of Law Number 1 of 1974 and Article 14 of the Compilation of Islamic Law concerning the terms and pillars wedding. The second consideration is that Petitioner I and Petitioner II have no obstacles to marriage as regulated in Article 8 of Law Number 1 of 1974 and Article 39 of the Compilation of Islamic Law. Based on the consideration of the evidence and the two witnesses presented, the panel of judges decided to grant the marriage Isbat proposed by the applicant.